Air pollutants and energy pathways : Extending models for abatement strategies - Syri, Sanna (Finnish Environment Institute, 2013)
This study presents the development and applications of regional and local scale models for use in integrated assessment of air pollution effects in conjunction with large-scale models. A regional deposition model called DAIQUIRI (Deposition, AIr QUality and Integrated Regional Information) for integrated assessment purposes in Finland was constructed, and regional matrices for nitrogen oxides and ammonia were developed from the results of the regional air quality model of the FMI. DAIQUIRI produced similar estimates of deposition from Finnish sources as the original model, and long-term trends and the average level of deposition estimated with DAIQUIRI were found comparable with the monitored deposition levels and trends. For the mid-nineties situation, the regional nitrogen modeling resulted in 9% to 19% (depending on the region compared) larger estimates of areas with acidity critical load exceedances than when using European scale nitrogen deposition modeling.In this work, also a method for estimating the impacts of local NOx emissions on urban and sub-urban ozone levels was developed and tested. The study concentrated on representing the destruction of ozone by fresh NO emissions in urban areas for future use in integrated assessment modeling of ozone control strategies. Correlation coefficients between measured daytime ozone values in the study area were found to improve from 0.64 (correlation between urban and surrounding rural measurements) to 0.85, on the average. The average correlation between daytime large-scale model estimates and urban site measurements was found to improve from 0.37 to 0.58.In the study, also integrated assessment model applications were carried out at European, national and local levels. The synergies between control strategies for CO2 and acidification and ozone formation in the case of the UN/FCCC Kyoto protocol and the air quality targets of the EU were assessed with the help of coupled models. With two alternative energy scenarios reflecting the Kyoto targets for CO2, ...